Justice by Faith and Eco-justice: Contours of a Life in the Spirit before the Ecocide (of the) Unlimited - Beros, Daniel Carlos (Scriptura, 2025)
This essay critically examines Christian spirituality in the context of the global ecological crisis, arguing that the prevailing "spirit of the unlimited" under financial capitalism drives ecological destruction and social injustice. Drawing on Pope Francis’ Laudato Si’ and Reformation theology, the author contends that Christian faith—particularly the "liberating limit" introduced through justification by faith—offers a decisive interruption to the destructive logic of unlimited expansion. The essay critiques the technocratic paradigm and neocolonial practices in the Global South, highlighting the lived realities of communities affected by extractive industries. It further interrogates the limitations of Laudato Si’s theological framework, suggesting that a more robust Christological and ecclesiological grounding is needed. Ultimately, the essay proposes that authentic Christian spirituality, rooted in communal worship and the transformative power of the Spirit, calls for resilient, solidaristic commitment to eco-justice, integrating care for creation with justice for the marginalised as a witness to the justice of faith.